Coordinated Control of ESP-SAS System Considering Roll. (28th December 2022) - Wang, Peng; Ge, Yuan; Cao, Shanggui; Han, Chao; Yang, Ping; Zhang, Zhichao
Abstract : To improve the antiroll ability of the vehicle, considering the coupling characteristics of vehicle dynamics and tire force, this paper proposes a vehicle active antiroll strategy based on an electronic stability program and semiactive suspension (ESP-SAS) coordinated control. According to the motion characteristics of the electronic stability program (ESP) and semiactive suspension (SAS), the fuzzy controller based on the ESP module and the proportion integration differentiation (PID) controller based on the SAS module are designed, respectively. Through the adjustment of ESP yaw moment and the timely matching of SAS damping force, the antiroll performance of the vehicle is optimized. At the same time, due to the coupling characteristics between the two, a coordinated controller is designed to minimize the transfer of tire dynamic load. The proposed strategy is simulated and verified by Fishhook test conditions. As is shown from the results, with a good effect on the control of vehicle roll risk, the proposed coordinated control strategy can not only effectively reduce the body roll angle but also improve the operation stability of the vehicle.